N, O-Dialkyl deoxynojirimycin derivatives as CERT START domain ligands. Issue 2 (15th January 2020) - Castellan, Tessa; Santos, Cécile; Rodriguez, Frédéric; Lepage, Mathieu L.; Liang, Yan; Bodlenner, Anne; Compain, Philippe; Génisson, Yves; Dehoux, Cécile; Ballereau, Stéphanie
Graphical abstract: Abstract: Dysregulation of the ceramide transport protein CERT is associated to diseases such as cancer. In search for new CERT START domain ligands, N -dodecyl-deoxynojirimycin ( N -dodecyl-DNJ) iminosugar was found to display, as a ceramide mimic, significant protein recognition. To reinforce the lipophilic interactions and strengthen this protein binding, a docking study was carried out in order to select the optimal position on which to introduce an additional O -alkyl chain on N -dodecyl-DNJ. Analysis of the calculated poses for three different regioisomers indicated an optimal calculated interaction pattern for N, O3 -didodecyl-DNJ. The two most promising regioisomers were prepared by a divergent route and their binding to the CERT START domain was evaluated with fluorescence intensity (FLINT) binding assay. N, O3 -didodecyl-DNJ was confirmed to be a new binder prototype with level of protein recognition in the FLINT assay comparable to the best known ligands from the alkylated HPA-12 series. This work opens promising perspectives for the development of new inhibitors of CERT-mediated ceramide trafficking.